Proteomic Analysis of Saliva in Patients with Oral Squamous Cell Carcinoma: Identifying Diagnostic and Prognostic Biomarkers in Indonesia - Rachmat Hidayat; Johan Wirahadi Putro; Arsan Saliha (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Oral squamous cell carcinoma (OSCC) is a significant health problem in Indonesia, characterized by high morbidity and mortality rates. Early detection is critical for improving patient outcomes. Saliva, a readily accessible biofluid, holds promise as a non-invasive source for identifying biomarkers for OSCC diagnosis and prognosis. This study aimed to identify salivary proteomic biomarkers associated with OSCC in an Indonesian population. Methods: Saliva samples were collected from 50 OSCC patients and 50 healthy controls. Proteomic analysis was performed using liquid chromatography-mass spectrometry (LC-MS/MS). Differentially expressed proteins were identified and validated using enzyme-linked immunosorbent assays (ELISA). Bioinformatic analysis was conducted to explore the functional roles and pathways associated with identified biomarkers. Results: LC-MS/MS analysis revealed 100 differentially expressed proteins in the saliva of OSCC patients compared to controls. After validation by ELISA, five proteins consistently showed significant differences: Increased levels of S100A7, MUC5B, and IL-6, and decreased levels of Statherin and Histatin 1 were observed in OSCC patients. Conclusion: This study identified a panel of salivary protein biomarkers with potential for OSCC diagnosis and prognosis in the Indonesian population. Further validation in larger cohorts is needed to assess their clinical utility and develop potential screening tools.